Chemical characterization of three Thymus species: T. herba-barona, T. pseudolanuginosus and T. caespititius - Fernandes Afonso, Andrea Luísa (2017)
The genus Thymus, belonging to Lamiaceae family, is rich in medicinal and aromatic species and well-known by several health promoting activities [1,2]. Despite this genus has been extensively studied, some species remain unexploited. In this study, Thymus herba-barona, Thymus pseudolanuginosus and Thymus caespititius decoctions were screened for their phenolic constituents by ultra-high performance liquid chromatography coupled to diode array detector and an electrospray mass spectrometer (UHPLC-DAD-ESI-MSn) operating in negative mode. The three aqueous extracts were rich in caffeic acid derivatives, mainly rosmarinic acid (MW 359) and its structural isomers, that accounted for 55.8 ± 2.8 mg/g in T. herba-barona and 40.2 ± 0.9 and 43.2 ± 3.2 mg/g in T. pseudolanuginosus and T. caespititius, respectively. In turn, other depsides were differently distributed in the three Thyme extracts: while dihydro-salvianolic acid B (MW 716 Da) and caffeoyl rosmarinic acid were particularly representative in T. herba-barona, salvianolic acids K ([M-H]− at m/z 555 493 359) and B ( [M-H]− at m/z 717 519 475) were found in moderate amounts in T. caespititius extract. On the other hand, T. pseudolanuginosus was clearly distinguished by its richness in the flavone luteolin-O-glucuronide ([M − H]− at m/z 461→285). Overall, this work is an important contribution for the phytochemical characterization of these three Thymus species, which are poorly explored.